2015
DOI: 10.1016/j.exphem.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of myeloproliferative neoplasms

Abstract: Major progress has been recently made in understanding the molecular pathogenesis of myeloproliferative neoplasms (MPN). Mutations in one of four genes-JAK2, MPL, CALR, and CSF3R-can be found in the vast majority of patients with MPN and represent driver mutations that can induce the MPN phenotype. Hyperactive JAK/STAT signaling appears to be the common denominator of MPN, even in patients with CALR mutations and the so-called "triple-negative" MPN, where the driver gene mutation is still unknown. Mutations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 133 publications
2
89
0
2
Order By: Relevance
“…Philadelphia-chromosome or BCR-ABL1 negative myeloproliferative neoplasms (MPNs) represented by polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are characterized by increased proliferation of erythroid, megakaryocytic, or granulocytic cells [1]. Major progress has been recently made in understanding the molecular pathogenesis of MPNs.…”
Section: Introductionmentioning
confidence: 99%
“…Philadelphia-chromosome or BCR-ABL1 negative myeloproliferative neoplasms (MPNs) represented by polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF) are characterized by increased proliferation of erythroid, megakaryocytic, or granulocytic cells [1]. Major progress has been recently made in understanding the molecular pathogenesis of MPNs.…”
Section: Introductionmentioning
confidence: 99%
“…1 CALR mutations were discovered in 50% to 80% of patients with JAK2 and MPL wild-type essential thrombocythemia (ET) and primary myelofibrosis (PMF), representing 20% to 35% of all patients with ET and PMF. This discovery was a landmark finding in understanding the pathogenesis of JAK2-and MPL-negative MPNs.…”
mentioning
confidence: 99%
“…However, variants in other genetic regions are also common, including CALR exon 9 (;25% ET, ;35% PMF), MPL exon 10 (;4% PMF, ;1% ET), and JAK2 exon 12 (;4% PV). [184][185][186][187][188] All those aberrations are part of diagnostic criteria in MPN and represent attractive targets for MRD monitoring. 189 For tracking of JAK2 V617F, qPCR currently represents the most reliable and sensitive method (;0.01%) and is widely used in clinical trials and routine laboratories to assess patient outcomes.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%
“…183,[195][196][197][198] HTS-based approaches are not broadly established yet for routine MPN molecular diagnostics, but their capacity to simultaneously cover multiple genetic variants make them a promising tool for monitoring the genetic complexity of MPN. 184,185,197 Abdelhamid et al demonstrated in a proof-of-principle study robust detection of JAK2 V617F in PB by HTS with high concordance to qPCR, even at low AFs. 199 Lundberg et al applied a targeted HTS panel (104 genes) to serial blood samples and showed that the number of emergent mutations over time was low, characterizing these diseases as genetically stable.…”
Section: Chronic Myeloid Leukemiamentioning
confidence: 99%